V. I. Lenin on the Constructive Character of Cognition - Meškauskas, Eugenijus (Problemos, 1970)
When developing creatively the Marxist theory of cognition V. I. Lenin gave much consideration to the elucidation of the dialectical character of the process of reflection. Lenin’s theory of cognition occupies a solid place in the content of Marxist philosophy. The essence of this theory, however, is not always correctly understood even in the Marxist philosophical literature. In such cases what is underlined is only the moment of reflection, whereas the dialectical character of this process is being disregarded. Such misinterpretation becomes apparent mostly when the concept of reflection is indiscriminately applied to the forms of cognitive thinking and sensual perception of reality. Lenin, meanwhile, not only did distinguish these forms of reflection but he would emphasize the class character of the distinction. The distinctive feature of the cognitive process as a special form of reality reflection is its social-historical and creatively constructive character. The paper gives proofs to the above-mentioned interpretation of Lenin’s theory of reflection.